Investment, Earnings Management and Equity-based Compensation - Chunwei Xian; Hong Chen; Asel Moldousupova (Journal of Accounting, Business and Management (JABM), 2011)
This study investigates the moderating effect of equity-based compensation incentives on the relationship between earnings management and investment. Previous studies have shown that there is a significant positive relationship between earnings management and investment decision making. Although investment opportunities signal high growth of firms, it is not a good indicator for these high-investment firms also have a high degree of earnings management. Based on agency theory, equity-based compensation can align the interests between shareholders and managers. It is possible that equity incentives may encourage optimal investment decisions by restraining earning management. We hypothesize that equity-based pay will decrease the degree of earnings management that is related to investment. We run OLS regressions of the interaction of equity-based compensation and investment on discretionary accruals by using the databases from COMPUSTAT and ExecuComp. We find that earnings management is less related to investment when the CEOs have been granted a large portion of equity-based pay. Equity-based compensation incentives can, then, decrease the tendency for earnings management and improve the efficiency of investment decision making. In addition, we find evidence that one of the components of equity-based compensation, stock options, positively affects the relation between earnings management and investment decision making. In contrast, the other component of equity-based compensation, restricted stock, has no significant influence on earnings management and investment. These results demonstrate that the stock options of executive compensation have a stronger moderating effect than the restricted stock of executive compensation on the relationship between earnings management and investment.